PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN YANG DI MODERASI OLEH KEPUASAN PELANGGAN (STUDI PADA KAPAL PENUMPANG KM. GUNUNG DEMPO PT. PELNI (PERSERO) - Risky Damayanti (2023)
This study aims to determine whether there is an influence of service quality and corporate image on customer satisfaction, service quality and corporate image on customer loyalty, and customer loyalty on customer satisfaction. Case study on the passenger ship KM. Mount Dempo PT. PELNI (PERSERO). This research uses descriptive research with a quantitative approach, which is measured using the PLS-R model with Smart PLS 4. The population of this study is KM passengers. Mount Dempo PT. PELNI (PERSERO). The sample is determined based on the calculation of the lemeshow formula, with a total of 120 samples on ship passengers. This data is used in research, in the form of secondary data. Data collection techniques used the documentation method in the form of books, journals and websites to test the hypothesis using the outer model test, Inner Model Test, Validity Test, Reliability Test, Statistical T Test, Probability Values Test and R Square. Based on the results and partial discussion shows that service quality has a significant positive effect on customer satisfaction, corporate image has a significant positive effect on customer satisfaction, service quality has a significant positive effect on customer loyalty, corporate image has a significant positive effect on customer loyalty, and customer loyalty has a positive effect on satisfaction customer.